Importância clínica de um estudo de bioequivalência entre duas formulações de diclofenaco sódico de liberação prolongada - Lima, Marinus de Moraes (2013)
Diclofenac sodium is a non-steroidal anti- inflammatory drug that exerts its effects through inhibition of cyclooxygenase and modulation of arachidonic acid; it has analgesic properties and is used for symptomatic treatment of pain, mainly related to inflammation. It is a drug widely used and easily accessible to the user. A bioequivalence study refers to the statistical comparison of the main pharmacokinetic measures observed in the experiment concerning to the products to be tested. This study aimed to evaluate the bioequivalence between a formulation of diclofenac sodium extended-release 100 mg capsules, called test formulation, versus a formulation of diclofenac sodium extended-release 100 mg capsules reference product, in healthy volunteers of both sex, fasted and fed, as recommended by ANVISA. Open-type Clinical trial, randomized , crossover, with four periods, two sequences, in which participants received in each distinct period in fasting or fed, 01 extended-release capsule of the test formulation or 01 extended release 100 mg capsule of diclofenac sodium of the reference formulation. In each hospitalization, the volunteers received the test or reference formulation with or without a specific diet pattern. The formulations were administered in a single oral dose, followed by blood sampling, at least four half-lives of study drug. Treatment periods obey an interval of seven half-lives, between then (washout). The diclofenac concentrations in plasma were dosed by a specific and validated analytical method based on liquid chromatography high efficiency coupled to mass spectrometry (LC-MS/MS). The results showed that with regard to AUCinf (area under the curve), the drugs were not bioequivalent to the extent of absorption. The peak plasma concentration (maximum concentration), which indicates the rate of absorption of the drug, was not bioequivalent between the test formulation and reference formulation, being outside the confidence interval of 80-125%. Considering the wide open use of diclofenac, it emphazises the importance of evaluate cost-efficiency versus cost-effectiveness when it guides the use of certain formulation of the market. The non therapeutic equivalence can compromise the treatment of a particular symptom, or even a disease, which may lead to discrediting the drug chosen. It is important to note that each individual responds to a drug in different ways, according to biological variations thereof, both formulations tested may be effective, although not bioequivalent.